Transcription and RNA editing in a soluble in vitro system from Physarum mitochondria - Cheng, Yu-Wei (Oxford University Press, 2000)
The dissection of RNA editing mechanisms in Physarum mitochondria has been hindered by the absence of a soluble in vitro system. Based on our studies in isolated mitochondria, insertion of non-encoded nucleotides into Physarum mitochondrial RNAs is closely linked to transcription. Here we have fractionated mitochondrial lysates, enriching for run-on RNA synthesis, and find that editing activity co-fractionates with pre-formed transcription elongation complexes. The establishment of this soluble transcription-editing system allows access to the components of the editing machinery and permits manipulation of transcription and editing substrates. Thus, the availability of this system provides, for the first time, a means of investigating roles for cis-acting elements, trans-acting factors and nucleotide requirements for the insertion of non-encoded nucleotides into Physarum mitochondrial RNAs. This methodology should also be broadly applicable to the study of RNA processing and editing mechanisms in a wide range of mitochondrial systems.